Analisis Kepuasan Pengguna Pada Aplikasi Tokopedia Menggunakan Metode User Experience Questionnaire (UEQ) - Anne Trimaysella; M. Rudi Sanjaya; Ibrahim, Ali (AI Society & STMIK Indonesia, 2024)
Tokopedia is an official application that was launched to the public on August 17 2009 under the auspices of PT. Tokopedia was founded on February 6 2009 by Wiliam Tanuwijaya and Leontinus Alpha Edition. Tokopedia is a platform that makes online shopping easy by offering a variety of products ranging from fashion, electronics, basic necessities and other daily necessities. However, judging from recent PlayStore and AppStore reviews, the Tokopedia application has received many negative reviews from users regarding the new features provided, one of which is the voucher and promo feature which cannot be used and other features. Therefore, evaluating the user experience while using this application is necessary. So user satisfaction analysis can be carried out using the User Experience Questionnaire (UEQ) approach to determine the level of satisfaction of Tokopedia mobile users. Therefore, the purpose of this research is to help conclude the information system regarding the Tokopedia application to improve experience and determine user satisfaction in carrying out further development and evaluation.